Biomechanical evaluation of hMSCs-based engineered cartilage for chondral tissue regeneration. (October 2018) - Gullotta, Fabiana; Izzo, Daniela; Scalera, Francesca; Palazzo, Barbara; Martin, Ivan; Sannino, Alessandro; Gervaso, Francesca
Abstract: Articular cartilage regeneration is still an open challenge in the field of tissue engineering. Although autologous chondrocytes seeded on collagen scaffolds (CSs) have already showed interesting results in the long-term repair of chondral lesions, they are not exempt from disadvantages that could be overcome using mesenchymal stem cells (MSCs). The ability of polymeric scaffolds to support MSCs proliferation and differentiation has been widely documented. However, few studies assessed their mechanical performances and additionally performing a single mechanical test, i.e. stress-strain or stress-relaxation in compression. Articular cartilage, though, possesses unique and multifaceted mechanical properties that can be exhaustively described only implementing a complete set of mechanical tests. Hence, the final aim of this study was to in depth assess the mechanical properties of human MSCs-cultured collagen scaffolds applying unconfined stress-strain, stress-relaxation and dynamic compression tests and identify key mechanical parameters. Firstly, plain CSs were fabricated and cultured under chondrogenic conditions with human MSCs (hMSCs). CSs displayed a high-interconnected porosity permitting uniform hMSCs distribution along the scaffold depth. Within CSs, hMSCs differentiated in chondroblasts, characterized by the presence of the lacunae and by a pericellular matrix positive for GAGs and for type 2 collagen deposition. The deep implemented mechanical characterization highlighted that the engineered constructs display (i) higher resistance to compression, (ii) more marked viscoelastic behavior over time and (iii) increased dynamic properties compared to naked CSs. In particular, stress-strain testes showed significant increase in the engineered constructs' stiffness that can be related to the proteoglycan deposition, observed by histology at the end of culture. Stress-relaxation and dynamic tests pointed out a substantial increase of peak and equilibrium stresses, relaxation time and dynamic modulus in the engineered constructs compared to empty CSs, suggesting a considerable decrease in scaffold permeability due to a strong chondral matrix deposition. Overall, the obtained results indicate a significant improvement of cell/CS mechanical performance toward a cartilage-like mechanical behavior. Graphical abstract: fx1 Highlights: 3D collagen scaffolds (CSs) were fabricated by freeze-drying and characterized. hMSCs homogeneously infiltrated and adhered on CS forming viable cells layers. CS enabled homogeneous chondrogenic maturation free of necrotic core. Pericellular matrix was positive for GAGs and type 2 collagen deposition. Engineered constructs showed higher static, viscoelastic, dynamic properties.